0
$\begingroup$

In an exercise, I have derived that

$$\mathrm dS_\mathrm{m} = \frac{3R}{2T}\mathrm dT + \frac{R}{V}\mathrm dV$$

using the 1st and 2nd law of thermodynamics (1 mol ideal gas).

Now, I want to write $\mathrm dS$ as a function of $T$ and $P$ instead of $T$ and $V$. How can I do that?

I have tried to do this:

$$\frac{R}{V} = \frac{P}{T}$$

and

$$\mathrm dV = \frac{\mathrm dV}{\mathrm dP}\mathrm dP = -\frac{RT}{P^2}\mathrm dP$$

This gives me

$$\frac{R}{V}\mathrm dV = -\frac{R}{P}\mathrm dP,$$

which is wrong according to my T.A.

How can I write $\mathrm dS$ as a function of $T$ and $P$?

$\endgroup$
  • 1
    $\begingroup$ When differentiating, are you sure $T$ was supposed to be treated as constant? I think this is correct: $$dV=\frac{R.dT}{P}-\frac{RT.dP}{P^2}$$ (Obtained by directly differentiating $V=\frac{RT}{P}$) $\endgroup$ – William R. Ebenezer May 8 at 9:50
1
$\begingroup$

The short way is to proceed as noted in the comments. The equivalent long way is to start from the total differential for $S_m$ in terms of $p$ and $T$:

$$dS_m = \left(\frac{\partial S_m}{\partial p}\right)_Tdp + \left(\frac{\partial S_m}{\partial T}\right)_pdT$$

The second term is given by

$$ \left(\frac{\partial S_m}{\partial T}\right)_p = \frac{C_p}{T}=\frac{5R}{2T}$$

The first can be determined using the identity

$$ \left(\frac{dS_m}{dp}\right)_T = -\left(\frac{\partial V_m}{\partial T}\right)_p=-\frac{R}{p}$$

Substituting,

$$dS_m = \left(-\frac{R}{p}\right)dp + \left(\frac{5R}{2T}\right)dT$$

It is not difficult to show that this is equivalent to the result obtained by substituting

$$dV=\frac{R.dT}{P}-\frac{RT.dP}{P^2}$$

into the expansion in terms of $V$ and $T$ shown in the OP.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.